PENDAMPINGAN OPTIMALISASI MASJID BAITUL MUKMIN DUSUN KARANGREJO DESA TEMPURAN KECAMATAN SAWOO KABUPATAN PONOROGO - Abdullah Muslich Rizal Maulana; Mawardi Mawardi; Kanda Naufal Jauhar Gani; Mohamad Abiyyu Althof; Agus Dwi Prasetio; Teguh Somara; M. Ilham Londring Basoka (As-Sidanah, 2022)
Muslim religious life considered Masjid as central. As such, the development of the Masjid as a very core of Islamic activities was necessary to be done. Masjid Baitul Mukmin in the hamlet of Karangrejo, village of Tempuran, regency of Sawoo, district of Ponorogo was one of the Masjid located in a remote area, far from the city center of Ponorogo. Both its physical and societal environment showed the lack of community's understanding regarding divine values has to be owned by Masjid; rather than symbolizing the strength of religiosity, the community of Karangrejo seemed not to pay close attention to the management of Masjid Baitul Mukmin. This paper highlighted several issues related to the optimization of Masjid Baitul Mukmin, particularly regarding the worth of cleanliness and the benefits of congregation prayer through socialization, preaching, and gathering with the citizens of Karangrejo Hamlet during the process of community development in the form of student study service (KKN). This paper concluded that there were several improvements in the society's understanding of the values of Masjid as the service ended. Continuous assistance yet still needed in the future by the community.